2021
DOI: 10.1093/genetics/iyab094
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the notion of deleterious sweeps

Abstract: It has previously been shown that, conditional on its fixation, the time to fixation of a semi-dominant deleterious autosomal mutation in a randomly mating population is the same as that of an advantageous mutation. This result implies that deleterious mutations could generate selective sweep-like effects. Although their fixation probabilities greatly differ, the much larger input of deleterious relative to beneficial mutations suggests that this phenomenon could be important. We here examine how the fixation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…We note that there is currently some debate in the field on the possibility that F ST outliers could be caused by negative selection in various forms (see, e.g., Matthey-Doret and Whitlock 2019 ; Johri et al 2020 ; Schrider 2020 ). Although it has been argued that such an effect is unlikely to explain F ST outliers in real data ( Matthey-Doret and Whitlock 2019 ; Schrider 2020 ), our method will be similarly challenged by this effect, as the information used is very similar to that of F ST outlier scans.…”
Section: Discussionmentioning
confidence: 97%
“…We note that there is currently some debate in the field on the possibility that F ST outliers could be caused by negative selection in various forms (see, e.g., Matthey-Doret and Whitlock 2019 ; Johri et al 2020 ; Schrider 2020 ). Although it has been argued that such an effect is unlikely to explain F ST outliers in real data ( Matthey-Doret and Whitlock 2019 ; Schrider 2020 ), our method will be similarly challenged by this effect, as the information used is very similar to that of F ST outlier scans.…”
Section: Discussionmentioning
confidence: 97%
“…Second, it would provide a solution to Muller’s problem with mutation load (Muller 1950) as redundancy would act as a sink for deleterious mutations and modulate their effect on fitness and disease (Johri ret a1. 2021 ; Singh and Gupta 2020 ). Third, it would provide a (non-neutral) solution to Lewontin’s dilemma of too much molecular variation (Lewontin 1974 ) as pathway redundancy would free individuals and populations from dependency on current mutations and would store genetic variation, accumulated as “experience” in the form of pre-adaptation, for future use (Delbrück 1949 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative importance of demography and selection as determinants of genome wide diversity is currently hotly debated, and may vary extensively among species (Corbett-Detig et al 2015;Rousselle et al 2018;Pouyet and Gilbert 2019;Galtier and Rousselle 2020). It has been shown that selection and demography can leave very similar footprints on the genetic diversity of a population (Andolfatto and Przeworski 2000;Teshima et al 2006;Thornton and Jensen 2007;Johri et al 2021a). Disentangling the effects of demography and selection is therefore crucial to avoid erroneous inference of evolutionary scenarios from genomic data (Jensen et al 2005;Wares 2009; Mathew and Jensen 2015;Johri et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…His results rely on rigorous mathematical arguments based on diffusion theory, but no closed form solution is provided for the shape of a neutral sweep. Johri et al (2021a) described the valley of diversity occurring around a neutral fixation using an approach introduced for selective sweeps, assuming that the evolution of the allele frequency is that of a selected allele except in the initial stochastic phase. Here, we extend this work by inferring the dynamics of fixation of neutral alleles after a population contraction and we examine their effects on neighboring regions of the genome.…”
Section: Introductionmentioning
confidence: 99%